The political economy of investment arbitration - Williams, Zoe Phillips (Oxford : Oxford University Press, 2022)
Zoe Williams' book examines the ways in which domestic politics contributes to the emergence of international legal disputes that have far-ranging consequences for states and citizens. More broadly, it illustrates how globalization clashes with democratic decision-making and state sovereignty.
This edition also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 1, 2022).
Keywords: Dispute resolution (Law); Arbitration and award; Investments, Foreign -- Law and legislation; Investments, Foreign -- Political aspects; Law; Laws of specific jurisdictions & specific areas of law